Harmonisasi kurikulum humanistik dengan kurikulum berbasis cinta di madrasah ibtidaiyah - Laila, Dwi Nur (Maliki Interdisciplinary Journal, 2026)
This article discusses the harmonization of the humanistic curriculum and the love-based curriculum in madrasah ibtidaiyah (Islamic elementary schools). By focusing on the concepts of the humanistic curriculum and the love-based curriculum, the article explores the philosophical foundations of both approaches. The harmonization between these two curriculum approaches lies in their shared perspective that views students as human beings with innate potential to be developed maximally and optimally. As a result, students are more focused on the holistic learning process, rather than solely on the cognitive domain. Thus, the affective and psychomotor domains can also be accommodated through the integration of the humanistic curriculum and the love-based curriculum within the learning process.